2009
DOI: 10.1002/ijc.24877
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Merkel cell polyomavirus (MCPyV) in Merkel cell carcinoma cell lines: Cell morphology and growth phenotype do not reflect presence of the virus

Abstract: The recently discovered human polyomavirus (MCPyV) is frequently found in Merkel cell carcinoma (MCC) tissue and is believed to be causally linked to MCC pathogenesis. While cell lines established from MCC represent a valuable tool to study the contribution of MCPyV to MCC pathogenesis, hitherto only 1 MCPyV‐positive line has been described. We have analyzed 7 MCC cell lines for the presence, integration pattern and copy number of MCPyV. In 5 cell lines, MCPyV specific sequences were detected. In 3 of these li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 24 publications
4
58
2
Order By: Relevance
“…A number of findings suggest a causative role of MCPyV in Merkel cell carcinoma tumorigenesis: the virus can be identified in the majority of MCC biopsy specimens (3,4,(6)(7)(8)(9), MCPyV DNA is monoclonally integrated in the tumor cells (3,9), the viral T-Ags are expressed in tumor cells (5,10), and LT-Ag sequences isolated from tumor cells harbor tumor-specific muta- tions that lead to premature truncation of LT-Ag, presumably due to a selection pressure to abrogate viral replication (9,18,64,65). It is striking that all truncated LT proteins retain the LxCxE motif, a fact that would seem to provide a strong argument for a dominant requirement for LT-Ag-mediated Rb inactivation during MCC pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of findings suggest a causative role of MCPyV in Merkel cell carcinoma tumorigenesis: the virus can be identified in the majority of MCC biopsy specimens (3,4,(6)(7)(8)(9), MCPyV DNA is monoclonally integrated in the tumor cells (3,9), the viral T-Ags are expressed in tumor cells (5,10), and LT-Ag sequences isolated from tumor cells harbor tumor-specific muta- tions that lead to premature truncation of LT-Ag, presumably due to a selection pressure to abrogate viral replication (9,18,64,65). It is striking that all truncated LT proteins retain the LxCxE motif, a fact that would seem to provide a strong argument for a dominant requirement for LT-Ag-mediated Rb inactivation during MCC pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Coding sequences for truncated SV40 LT and MCPyV LT were PCR amplified using pZIPTEX (33) or cDNA from the MCPyV-positive MCC cell line 12 (18) as the template, and PCR fragments were sequenced and subcloned into pRSETA (Invitrogen). Nterminal His-tagged proteins were expressed in BL21 Star in LB medium supplemented with 1% glucose at 37°C for 4 h using 1 mM isopropyl-␤-D-thiogalactopyranoside (IPTG; for SV40 LT) or at 16°C for 18 h using 0.5 mM IPTG (for MCPyV LT).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The classification of MCC cell lines is made under the name of "classical" and "variant" phenotypes. These phenotypes are further divided into subtypes based on morphology and expression of genes taken neuroendocrine markers [62]. It has been suggested that the classical phenotype is for the MCC MCV-positive strains, and the MCV-negative strains are the variant [43].…”
Section: And MCC Associationmentioning
confidence: 99%